1997
DOI: 10.1111/j.1399-0004.1997.tb02566.x
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Partial trisomy of 15q due to inserted inverted duplication

Abstract: A de novo abnormal chromosome 15, with an inverted duplication of the segment (15q13.3 → 15q21.3) at 15q24.3, was found in a boy with mild developmental delay, facial dysmorphism, Marfan‐like appearance and severe language delay. There is an unusual disparity between the severe lack of speech and the presence of reasonable skills in other areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The second chromosome involved in the reciprocal translocation has varied; chromosomes 2, 7, 8, 11, 13, 15 (Robertsonian translocation), and 21 have been reported6). Other cases of 15q duplication have been the result of direct or inverted duplication14,15). However, in this case, there were no concomitant translocations or deletions.…”
Section: Discussionmentioning
confidence: 73%
“…The second chromosome involved in the reciprocal translocation has varied; chromosomes 2, 7, 8, 11, 13, 15 (Robertsonian translocation), and 21 have been reported6). Other cases of 15q duplication have been the result of direct or inverted duplication14,15). However, in this case, there were no concomitant translocations or deletions.…”
Section: Discussionmentioning
confidence: 73%
“…Elcioglu (1997) [ 12 ] and Herr (1983) [ 13 ] each reported a case with a de novo interstitial duplication on 15q13.3q21.3 and 15q14q21.1 respectively. The Decipher case 260222 largely overlapped with the duplication detected in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas duplications distal to 15q13 are very rare. Elcioglu (1997) described a patient with hypogonadism, skeletal anomalies, Marfan-like features, developmental delay and intellectual disability, who carried a de novo interstitial inverted duplication involving bands of 15q13.3-q21.3 [ 12 ]. Herr (1983) reported a patient with a de novo interstitial duplication of 15q14-q21.1, who presented with hypogonadism, skeletal problems, short stature, delayed bone age, global developmental delay and intellectual disability [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herr et al [1983] reported a 12-year-old boy with a de novo interstitial duplication of 15q14q21.1, who presented with scrotal hypoplasia and micropenis, short stature, seizure disorder, distinctive facial features, kyphosis and scoliosis, global developmental delay, and intellectual disability. Elçioglu et al [1997] described a patient with hypogonadism, dysmorphic facial features, hypotonia, developmental delay, Marfan-like features and intellectual disability, who carried a de novo interstitial inverted duplication involving bands 15q13.3q21.3. Recently, Yuan et al [2016] described an interstitial duplication of 15q15.3q21.1 in a 14-year-old boy with severe short stature, delayed bone age, hypogonadism, global developmental delay, and intellectual disability.…”
Section: Discussionmentioning
confidence: 99%